Kriteria Rekrutmen dan Seleksi Pendidik di Pondok Pesantren As-Sa'adiyah Samarinda - Ma’rifatul Hasanah; Rina Delvani; Vernalita Anata Dharmayanti; Afita Nur Hayati (Jurnal DinamikA, 2023)
This research aims to determine the recruitment system for educators at As-Sa'adiyah Islamic Boarding School in Samarinda. The research utilizes interview techniques by posing several questions directly to the interviewees, and employs a literature approach using scientific journals, books, articles, and other credible sources. The findings of this research indicate that in the recruitment process for prospective educators at As-Sa'adiyah Islamic Boarding School, the Foundation does not conduct an open recruitment process. Instead, it relies on a familial system, wherein individuals are invited to become teachers through connections with Ustadz, Ustadzah, educators, or staff members of the boarding school, as well as reputable alumni. However, the recruitment is based on competency standards, ensuring that the candidates are already competent in their respective fields.